An Analysis of English Learning Difficulties among Nursing Students (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
English plays an important role in supporting students’ academic learning and future professional practice. In nursing education, students are expected to use English to understand field-related terminology, communicate in learning and clinical contexts, and engage with academic sources relevant to nursing. To support these needs, English instruction is commonly delivered through an English for Specific Purposes (ESP) approach that focuses on language use within the nursing context. Nevertheless, questions remain regarding how far ESP-based instruction responds to the learning difficulties experienced by nursing students. Therefore, this study aims to analyze the English language learning difficulties experienced by undergraduate students in the Nursing Science Program at the University of Bhamada Slawi. This study conducted a descriptive qualitative research design. Data were collected through a learning needs questionnaire and limited interviews involving undergraduate students from the Nursing Science Program at the University of Bhamada Slawi. The findings demonstrate that undergraduate nursing students experience a wide range of English learning difficulties across multiple language skills. These difficulties indicate that students’ English learning needs are diverse and extend beyond general language competence. English is required not only to support students’ current academic activities, such as understanding nursing texts and participating in clinical communication, but also to prepare them for future professional practice in healthcare settings where English is increasingly used. Based on these findings English teachers and curriculum developers are encouraged to design instructional materials and learning activities that align with the academic and professional needs of nursing students.